EX VITRO ROOTING OF OIL PALM (Elaeis guineensis Jacq.) PLANTLETS DERIVED FROM TISSUE CULTURE - Sumaryono, Sumaryono; Riyadi, Imron (Indonesian Journal of Agricultural Science, 2011)
Plantlets of oil palm (Elaeis guineensis Jacq.) derived from so-matic embryos sometimes do not form well developed-roots. Root formation of unrooted-plantlets can be induced with aux-in during ex vitro acclimatization period to simplify the proce-dure and to reduce seedling production cost. Experiments were conducted using a completely randomized design to determine the effect of different types of auxin, i.e. indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), and 1-naphthalene-acetic acid (NAA) at different concentrations, i.e. 0, 2, 4, 8, and 16 mM on root development of oil palm plantlets. The plantlets used were derived from somatic embryos of MK 649 oil palm clone. The basal end of the shoots was dipped in auxin solution for 10 minutes before the shoot was cultured in a small plastic pot containing a mixed growing medium. The cultures were then placed inside a closed transparent plastic tunnel (240 cm x 100 cm x 95 cm) for 12 weeks. The results showed that without auxin treatment only 15% of the shoots formed roots. Dipping in auxin solution increased significantly root frequen-cy to more than 50%. The best root formation was found on the shoots treated with 2 mM NAA by which rooting frequency was 80%. Auxin treatments also increased root quality as indi-cated by more number of primary and secondary roots. IAA, IBA, and NAA treatments at all concentrations tested increased significantly shoot height on average by 42% and shoot diame-ter by 30% compared to control treatment, but did not influ-ence root length. The best treatment for inducing roots of oil palm plantlets ex vitro was by dipping the basal end of the plant-lets in 2 mM NAA solution. The result showed that rooting of oil palm plantlets could be successfully conducted ex vitro that would eliminate sterile rooting stage thus simplify the protocol and reduce seedling production time and cost.